Tangible Objects versus Digital Interfaces: Opportunities to Harness the Potential of Augmented Reality to Interact with Photographic Collections in Museums and Archives. Issue 2 (June 2018) - Forster, Ingrid
The use of augmented reality (AR) as an immersive and interactive engagement tool for art and cultural institutions is increasing. AR, when used in a meaningful way, has shown great potential for discovery-based learning experiences. In this article, I consider the potential of AR for photographic collections in museums and archives by addressing two key questions: How can digital tools like AR serve to enhance our understanding of photographs as both object and image? What are the implications and limitations of this technology when used for this purpose?